THE ASPECTS OF EDUCATION IN ANDREA HIRATA’S THE RAINBOW TROOPS - Rosa Maria Simamora; Sriviani Br Tarigan (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This study discusses the aspects of education in Andrea Hirata’s The Rainbow Troops. The novel is seen as the portrait of education in some remote Indonesian areas. This is a library research, and its theory is mimetic proposed by Abrams saying that literature is the imitation of the real life. This study focuses on the discussion of the lack of the aspects of education in Indonesia particularly in the remote areas. It is traced through educator characters represented by Bu Mus who has high dedication and effort to sincerely motivates and educates the students towards perfection, Learners are represented by The Rainbow Troops students who really need to develop themselves psychologically and physically, educational method represented by Bu Mus and Pak Harlan who set specified curriculum to achieve educational goals, educational materials and tools are materials or media used in teaching and learning process, and educational environment is everything that is visible in natural world of life which always develops. In conclusion, Andrea Hirata in his novel The Rainbow Troops vividly portrays the condition of education in remote areas with inadequate aspects of education but shows exemplary teachers and students, intelligence, fighting spirit in educating children and achieving goals.